Upaya Peningkatan Keterampilan Bermain Softball Melalui Pembelajaran Cultularry Resposive Teaching (CRT) pada Siswa Kelas X SMA Negeri 11 Semarang - Kusumaningtyas, Thania (Media Penelitian Pendidikan : Jurnal Penelitian dalam Bidang Pendidikan dan Pengajaran, 2025)
This research aims to find out efforts to improve softball playing skills through cultularry reposive teaching (CRT) learning in grade x students of SMA Negeri 11 Semarang. This research is categorized as a quantitative research that uses a quasi-experimental design approach. The research contains the impact of learning methods based on the culturally responsive teaching  approach with traditional games on the learning outcomes of softball throwing skills. A pretest-posttest design involving one group was used for this study. The research population consisted of students involved in class X learning at SMA Negeri 11 Semarang which amounted to 288 participants. The sampling technique applied is purposive sampling. So the same method used in this study is 36 students in class X.9. This study uses the test as an assessment test instrument for the softball catch. Normality tests, homogeneity tests, and hypothesis tests are some of the analyses used in the research. Before learning the culturally responsive teaching  approach with traditional games, the lowest score was 5, the highest score was 12, the average was 8.19 and the standard deviation value was 1.721. In the softball throwing and catching skills after learning the culturally responsive teaching  approach with traditional games, the lowest score was 5, the highest score was 13, the average was 10.38 and the standard deviation value was 1.715. The final score on the softball throwing skill before learning the culturally responsive teaching  approach with traditional games obtained the lowest score of 35, the highest score of 92, the average of 63.03 and the standard deviation value of 13.265. In the softball throwing and catching skills after learning the culturally responsive teaching  approach with traditional games, the lowest score was 46, the highest score was 100, the average was 83.25 and the standard deviation value was 13.135. Based on the results of the study, information was obtained that the improvement in softball throwing skills before and after learning the culturally responsive teaching  approach with traditional games experienced an average increase of 32.08%. The conclusion in this study is that the use of culturally responsive teaching  approach with traditional games has an effect on the learning outcomes of softball throwing skills. As for the suggestions that can be given in this research, for teachers, the use of game models in learning can increase student enthusiasm.